A Prototype of Garbage Picker Ship Robot Using Arduino Nano Microcontroller - Siregar, Ivana Maretha; Yunus, Muhammad; Siregar, Victor Marudut Mulia (Internet of Things and Artificial Intelligence Journal, 2022)
This study aims to create a robot prototype for a garbage collection ship made using an Arduino nano microcontroller. The prototype of this garbage collection robot vessel is controlled by an Android smartphone application that is connected via Bluetooth. The prototype of the robot of the boat was made to deal with piles of garbage that can cause flooding. The method used in making the prototype ship robot along with the controller application begins with identifying the problem, namely the problem of piles of garbage, then needs analysis. Moreover, in this research, what will be developed is in terms of design, ship robot prototype, and ship robot controller design. Next is implementation and testing. The prototype of the garbage collection ship robot uses an Arduino nano microcontroller and in making a controller application using Android Basic 4. Then the trial stage was carried out on an Android smartphone. The results of this study are a prototype ship robot that can move according to commands through a controller application.